PENERAPAN METODE LIGHTENING THE LEARNING CLIMATE DALAM MENINGKATKAN KEAKTIFAN SISWA KELAS VIII SMPN 5 BANTAN - Natasya, Natasya (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This research is motivated by the existence of learning methods used that are still ineffective so that students tend to be less active in the learning process. This study aims to find out how the lightening the learning climate method is applied. Then, to find out how much the application of the lightening the learning climate method in increasing the activity of class VIII students in Islamic Religious Education subjects at SMPN 5 Bantan. The type of research used in this study was an experiment by taking 2 classes from the population consisting of an experimental class and a control class. Data collection techniques using tests and documentation. This study concluded that after the lightening the learning climate method was applied, the implications for the implementation of student learning went well. This is because student activity becomes more optimal. The lightening the learning climate method can increase the activity of class VIII students in Islamic Religious Education subjects at SMPN 5 Bantan